2016
DOI: 10.1590/1982-43272664201604
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion in Relation to Self-Esteem, Self-Efficacy and Demographical Aspects

Abstract: This study investigated relationships between self-compassion, self-efficacy, and self-esteem, as well as age and sex differences and other sociodemographic variables in relation to self-compassion. Four-hundred and thirty-two Brazilian adults (50% women) from nearly all country states participated in the study filling out a sociodemographic survey and three scales: self-compassion, self-efficacy, and self-esteem. Comparisons of means between self-compassion and pairs of groups designed by sociodemographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
8
28
0
4
Order By: Relevance
“…Porém, as diferenças etárias não têm encontrado respaldo firme nas pesquisas da autocompaixão. O estudo de Neff e Vonk (2009) encontrou correlação significativa entre autocompaixão e idade em uma (Souza & Hutz, 2016b). Os dados do presente estudo repetem estas diferenças e parecem contribuir para apontar para diferenças etárias que merecem investigações mais detalhadas com respeito à autocompaixão.…”
Section: Discussionunclassified
“…Porém, as diferenças etárias não têm encontrado respaldo firme nas pesquisas da autocompaixão. O estudo de Neff e Vonk (2009) encontrou correlação significativa entre autocompaixão e idade em uma (Souza & Hutz, 2016b). Os dados do presente estudo repetem estas diferenças e parecem contribuir para apontar para diferenças etárias que merecem investigações mais detalhadas com respeito à autocompaixão.…”
Section: Discussionunclassified
“…In a Turkish university study, Iskender (2009) found a positive correlation between self-compassion and self-efficacy. Another study confirmed the association between self-compassion and self-efficacy using an adult sample (Sousa & Hutz, 2016). Another study confirmed the association between self-compassion and self-efficacy using an adult sample (Sousa & Hutz, 2016).…”
Section: Self-compassion As a Mediatormentioning
confidence: 61%
“…Students with high self-compassion reported having higher self-efficacy in accomplishing goals at school than students with low self-compassion (Iskender, 2009). Another study confirmed the association between self-compassion and self-efficacy using an adult sample (Sousa & Hutz, 2016). Another university study found that when students experience academic failures, self-compassionate students are more likely to feel confident about performing better in the future, which serves as a self-coping mechanism to successful academic behaviors (Manavipour & Saeedian, 2016).…”
Section: Self-compassion As a Mediatormentioning
confidence: 84%
“…Thus, self-compassion could be instrumental in the increase of self-efficacy. The positive relationship of self-compassion with self-efficacy has been reported in literature (de Souza & Hutz, 2016;Iskender, 2009).…”
Section: Self-compassion and Career And Talent Development Self-efficacymentioning
confidence: 79%